Antitrust policy in Europe - Swann, D.; Lees, D. ([S.l.] : Financial times)
This study provides businessmen with an up to date guide on Europe's antitrust laws and policies - what they are, how they work in practice and how British companies in particular may be affected
osc 24/09/2021
Loans
Keywords: Antitrust law; Europe